Existence and asymptotic behaviour for a degenerate kirchhoff-carrier model with viscosity and nonlinear boundary conditions - Cavalcanti, M.M.; Domingos Cavalcanti, V.N.; Soriano, J.A.; Prates Filho, J.S. (Revista Matemática Complutense, 2001)
Sin resumen